Aerosol Transmission of Coronavirus and Influenza Virus of Animal Origin - Lv, Jing; Gao, Jing; Wu, Bo; Yao, Meiling; Yang, Yudong; Chai, Tongjie; Li, Ning (Frontiers in Veterinary Science, 2021)
Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused great harm to global public health, resulting in a large number of infections among the population. However, the epidemiology of coronavirus has not been fully understood, especially the mechanism of aerosol transmission. Many respiratory viruses can spread via contact and droplets transmission, but increasing epidemiological data have shown that viral aerosol is an essential transmission route of coronavirus and influenza virus due to its ability to spread rapidly and high infectiousness. Aerosols have the characteristics of small particle size, long-time suspension and long-distance transmission, and easy access to the deep respiratory tract, leading to a high infection risk and posing a great threat to public health. In this review, the characteristics of viral aerosol generation, transmission and infection as well as the current advances in the aerosol transmission of zoonotic coronavirus and influenza virus are summarized. The aim of the review is to strengthen the understanding of viral aerosol transmission and provide a scientific basis for the prevention and control of these diseases.